Characterization of wrought aluminium feedstock billet produced by semisolid metal processing route - Benjunior, Bindamin (2021)
This thesis presents the research works on the characterization of aluminium 6061 feedstock billet produced through semisolid metal processing (SSMP) route. This thesis also aims to add, improves and brighten the knowledge of wrought aluminium 6061 feedstock billet behaviour, which was then thixoformed. The experimental works started with a Thermal Analysis (TA) experiment which conducted purposely to understand the relationship between fraction solid and temperature. TA experiment was conducted at three different cooling rate conditions consist of slow cooling (0.03 °C/s), medium cooling (0.2 °C/s) and fast cooling (0.3 °C/s). The information gained from TA was used to produce thixotropic feedstock billet via Direct Thermal Method (DTM). The pouring temperature and holding time for the DTM experimental works consisted of 660 °C and 20 s, 660 °C and 60 s, 700 °C and 20 s, 700 °C and 60 s respectively, with three samples were produced for each combination. The feedstock billet samples were then prepared for microstructure analysis, density and hardness test. These feedstock billet samples were then heated to a temperature of 610 °C and thixoformed. The hydraulic press machine parameters for thixoforming operation were set at 155 bars for hydraulic pressure and 15 s for holding time. Finally, the samples formability was observed. The results for TA found that an extensive range of temperature dropped occurred for the fraction solid range between 20 % and 40 % for cooling rate of 0.03 °C/s, compare to a cooling rate of 0.2 °C/s and 0.3 °C/s. The fraction solid for the cooling rates of 0.2 °C/s and 0.3 °C/s also has shown rapid fraction solid formation at 20 % at a higher temperature with a shorter time. However, it was less effective to maintain the fraction solid at 20 % with a very short range of temperature drop compared with 0.03 °C/s. The feedstock billet with a combination of pouring temperature 660 °C and holding time 20 s produced the most suitable microstructure for SSMP which has the smallest microstructure with the sample average area value size of 2797 μm². This pouring temperature was slightly above liquidus temperature that caused less superheat to be extracted which provided a slow cooling rate action during the solidification stage. Consequently, it promoted the formation of more grain nuclei and resulted in a smaller grain size. Hardness value also was found increased with the lower pouring temperature and holding time. Thixoforming experimental results show that a sample with the combination of pouring temperature 660 °C with a holding time of 20 s showed the most significant length filled the mould cavity with a less significant difference with other samples. These results have confirmed the existence of smaller and globular grain structure within the sample. It also proved that although the other parameters combination sample has better hardness and density value, the main factor to ensure SSMP accomplishment (formability) was the grain structure size and circularity of the feedstock billet. The conclusions of this study have documented that different cooling rates conditions altered the phase changes temperature with the increment of fraction solid, took a long time and at a lower temperature for a slow cooling rate condition. Pouring temperature of 660 °C with a holding time of 20 s produced a better fine globular and uniform microstructure. These findings could give a better understanding of the material behaviour which could lead to a better manufacturing operation, equipment design and precise parameters needed to ensure the success of SSMP.